Destination Attractiveness and Visit Intention: Integrating Image, Cultural Experience, and Sustainable Practices in Tourist Decision-Making - Goeltom, Andar Danova L.; Hurriyati, Ratih (Journal of Tourism, Hospitality and Travel Management, 2024)
In the increasingly competitive landscape of global tourism—particularly in the post-COVID-19 era—destination attractiveness has emerged as a critical factor shaping tourist perceptions and behavioral intentions. This study investigates the combined effects of digital engagement, perceived safety, destination image, sustainable practices, and cultural experience on destination attractiveness and visit intention. Grounded in cognitive-affective image theory, value-belief-norm theory, and the technology acceptance framework, a conceptual model was empirically tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) on data collected from 368 valid respondents. The results reveal that digital engagement significantly enhances both perceived safety and destination image, while sustainable practices positively influence cultural experience and attractiveness. Destination image and cultural experience also emerge as key mediators in the formation of destination attractiveness. Most notably, destination attractiveness strongly predicts visit intention, underscoring its central role in tourism decision-making. This study contributes to tourism literature by integrating digital, sustainability, and experiential factors into a unified framework, offering a more nuanced understanding of how contemporary tourists evaluate and commit to destinations. Practical implications highlight the importance of leveraging digital platforms, promoting transparent safety measures, and embedding sustainability into tourism development strategies. The findings provide actionable insights for destination management organizations aiming to foster long-term competitiveness in a values-driven and experience-focused tourism market.